Output-based Arabic Language Learning in The Excellent Class of Islamic Junior Highschool in Tulungagung - Faruq, Umar; Nurcholis, Ahmad; Efendi, Heri; Laila, Izzatul; Hidayatullah, Syaikhu Ihsan (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
People spend about 6 hours a day using a gadget, and if it is not controlled properly, their handphones can lead to negative impacts. As the answer, students today are different from learners in the past who focus more on routine activities by reading written sources. In this modern era, they have various accesses to determine the learning resources they want and need for themselves. Furthermore, optimizing ICT use is the main priority in improving Arabic learning quality. It is qualitative research. The study results show that the Arabic language teaching-learning process in the excellent class of MTsN 6 Tulungagung has been using various ICT media. Its implementation has some problems, including the lack of facilities or infrastructure and the teachers' problem in mastering technology. This research indicates that using ICT is one step forward in the world of education.